Navigating the Photographic Periphery: Vivian Maier and Amateur Photography - Mounfield, Lucy (2022)
This thesis is concerned with the ways in which women are subject to and limited by gendered categorisations of photographic practice. The photography of Vivian Maier (1926-2009) will form a case study arguing that Maier’s photographic practice and posthumous recognition is representative of the marginalisation of women in photography, which has in turn led to an erasure of women photographers in photographic histories. The impetus for the construction of a reputation as a ‘street photographer’ for Maier is located in the economic imperatives governing the collectors and exhibitors of her work, whilst the necessary attributes of that reputation are determined by canonical values that eschew difference. The thesis will re-think the binaries of inside-outside and amateur-professional using Foteini Vlachou’s conceptualisation of centres and peripheries put forth in her article, Why Spatial? Time and the Periphery (2016) in order to show that the historiography of American photography is underpinned by sexual difference.